2016
DOI: 10.17796/1053-4628-40.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Prevalence of Pre-Eruptive Intracoronal Radiolucent Defects in the Permanent Dentition

Abstract: The prevalence of pre-eruptive intracoronal lesions was not higher for young age groups. The prevalence of pre-eruptive intra coronal radiolucent lesions is 3.9%, irrespective of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 7 publications
5
22
3
1
Order By: Relevance
“…The lack of a significant difference in PEIR prevalence between the sexes also corresponded to the prevalence in previous studies . The highest patient prevalence in a previous study was in a Malaysian population (27.3%), whereas most other studies reported patient prevalence to be lower than 10% (0.85%‐8.1%) (Table ) . The different prevalences between studies could be due to differences in ethnicity, the types of teeth examined, or the age range of the population (Table ).…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…The lack of a significant difference in PEIR prevalence between the sexes also corresponded to the prevalence in previous studies . The highest patient prevalence in a previous study was in a Malaysian population (27.3%), whereas most other studies reported patient prevalence to be lower than 10% (0.85%‐8.1%) (Table ) . The different prevalences between studies could be due to differences in ethnicity, the types of teeth examined, or the age range of the population (Table ).…”
Section: Discussionmentioning
confidence: 51%
“…reported that PEIR were not present in a younger age group (4‐8 years, 0%) whereas they were almost equally present in intermediate (9‐12 years, 46.2%) and adult age groups (13‐53 years, 53.8%) . Additionally, the patient prevalences in more recent studies, which had expanded population age ranges, were not much different from those in younger populations (Table ). Consequently, the wide variations in the reported patient prevalence might not be affected by differences in age range included in those studies, but rather, might result from differences in the samples in each study (ethnicity or the types of teeth examined) and different PEIR screening protocols (radiographic technique used, PEIR diagnostic criteria, diagnostic difficulties from radiographic quality, or examiner experience of this rare condition).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations